PENGEMBANGAN MEDIA AUDIO VISUAL PADA PEMBELAJARAN PAI BERBASIS MODEL ASSURE - Munarun, Ahmad; Anbiya, Bakti Fatwa (Journal Education and Government Wiyata, 2024)
The 21st century's digital revolution has had a significant effect on education as well. Media and instructional techniques also evolve to meet the demands of the moment. The implementation of the ASSURE model is one of the many learning models being explored to improve the efficacy of learning. The usefulness of the ASSURE learning paradigm and its implementation procedures for incorporating video content into Islamic religious education (PAI) are covered in this article. The author used a qualitative method with a literature study strategy in this investigation. Our main sources of information are books and articles about the ASSURE method's use and the efficacy of PAI learning. The article conclusion is that improving student interest and learning effectiveness can be achieved by combining the ASSURE learning model with instructional video materials. The ASSURE model's steps analyzing student characteristics, defining learning objectives, choosing instructional strategies and media, utilizing teaching materials, getting students actively involved in the learning process, and evaluating and revising help produce meaningful learning experiences and raise the standard of instruction overall. At the conclusion of the learning process, evaluation is crucial to determine how well the lessons were learned and to offer insightful criticism for future developments. As a result, issues with student engagement and learning ennui in religious education can be effectively resolved by utilizing the ASSURE learning model and learning resources like videos.